Oncologic outcome with versus without target volume compartmentalization in postoperative radiotherapy for oral cavity squamous cell carcinoma - Riggenbach, Elena; Waser, Manuel; Mueller, Simon A.; Aebersold, Daniel M.; Giger, Roland; Elicin, Olgun (Frontiers in Oncology, 2024)
Background and purpose: The volume treated with postoperative radiation therapy (PORT) in patients with oral cavity squamous cell carcinoma (OCSCC) is a mediator of toxicity affecting quality of life. Current guidelines only allow for very limited reduction of PORT volumes. This study investigated the safety and efficacy of deintensified PORT for patients with OCSCC by refined compartmentalization of the treatment volume.Materials and Methods: This retrospective cohort study identified 103 OCSCC patients treated surgically from 2014 to 2019 with a loco-regional risk profile qualifying for PORT according to guidelines. PORT was administered only to the at-risk compartment and according to a refined compartmentalization concept (CC). Oncological outcome of this CC cohort was compared to a historical cohort (HC) of 98 patients treated before the CC was implemented.Results: Median follow-up time was 4.5 and 4.8 years in the CC and HC cohorts, respectively. In the CC cohort, a total of 72/103 patients (70%) had a pathological risk profile that allowed for further compartmentalization and hence received benefitted from a reduced treatment volume or omission of PORT altogether. Loco-regional control at 3 and 5 years was 77% and 73% in the CC cohort vs. 78% and 73% in the HC (p=0.93), progression-free survival was 72% and 64% vs.75% and 68% (p=0.58), respectively. Similarly, no statistically significant difference was seen in other outcome measures.Conclusions: Deintensified PORT limiting the treatment volume to the at-risk compartment or avoiding PORT altogether for low-risk patients with OCSCC does not seem to compromise disease control in this retrospective comparison. Based on these hypothesis-generating findings, a prospective study is being planned.